2019
DOI: 10.1186/s40008-019-0176-9
|View full text |Cite
|
Sign up to set email alerts
|

Causal effect of mergers and acquisitions on EU bank productivity

Abstract: Over the last two decades, bank consolidation has been a frequent event in the financial sector in developing and developed countries, particularly in the European Union (Pozzolo 2009). Considering the subprime crisis, which negatively affected many advanced and emerging economies, particularly in the banking sector of the European Union, various solutions, such as mergers and acquisitions (M&A), have appealed to these countries. M&A represent external growth and approximately 80% of global foreign direct inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Revenue synergies also derive from a better combination of production factors which is mainly typical for economics with higher economic growth and volume of GDP. Finally, Aljadani and Toumi (2019) confirmed that the deregulation process in the banking industry, which has occurred mainly in most developed countries in the European Union, with the subsequent increase in the level of competition, forced banking entities to react to a new competitive scenario. Mergers and acquisitions were a frequent response in many developed European countries with higher volumes of GDP, and good management of the integration process and the consolidating banks clearly contributed to the success of mergers and acquisitions.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 66%
See 1 more Smart Citation
“…Revenue synergies also derive from a better combination of production factors which is mainly typical for economics with higher economic growth and volume of GDP. Finally, Aljadani and Toumi (2019) confirmed that the deregulation process in the banking industry, which has occurred mainly in most developed countries in the European Union, with the subsequent increase in the level of competition, forced banking entities to react to a new competitive scenario. Mergers and acquisitions were a frequent response in many developed European countries with higher volumes of GDP, and good management of the integration process and the consolidating banks clearly contributed to the success of mergers and acquisitions.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 66%
“…Mergers and acquisition helps the bank not only to get new brand name, new structures, product offerings but additionally give opportunities to cross sell the new accounts acquired (Subhashree and Kannappan, 2018;Gavurova et al 2017a,b). Specifically, several authors devoted to research in the framework of M&A in the banking sector, such as Teplý et al (2010); Ayadi and Arnaboldi (2008); Aljadani and Toumi (2019); Micu and Micu (2016), etc.…”
Section: Introduction and Theoretical Frameworkmentioning
confidence: 99%
“…Moksliniai tyrimai rodo (Smirnova, 2014;Li, 2016;Cortés et al, 2017;Aljadani & Toumi, 2019;Ahmed, 2020), kad susiliejimų ir įsigijimų priežastys yra įvairios; todėl tyrimuose paprastai randamas ne vienas, o keli įvykusio susijungimo motyvai ir priežastys. Bankiniame sektoriuje vykdomi susiliejimų ir įsigijimų sandoriai dažnai yra laikomi galimybe sumažinti bankinio sektoriaus pajėgumo perteklių, menką pelningumą ir padidinti bankų efektyvumą.…”
Section: Susiliejimų Ir įSigijimų Sandorių Sudarymo Priežastys Bankin...unclassified
“…They even indicate that "small regional banks would gain efficiency if they merge with neighbouring banks, whereas larger banks would gain efficiency when merging with distant banks" (Halkos et al, 2016, p. 47). Aljadani & Toumi (2019) have investigated the causal effect of mergers and acquisitions (M&A) on bank productivity in 23 European Union countries over the period 1990-2013. Their sample consists of 156 commercial banks, of which 60 entities have acquired at least one other entity.…”
Section: Literature Reviewmentioning
confidence: 99%